Perancangan Interior “House of VW” di Surabaya - Sheilly Jennie Laurianto; Grace Mulyono (Intra, 2014)
There’s a lot events in the automotive world, especially Volkswagen clubs bring the idea to accommodate all the activities associated with the brand. Volkswagen is a manufacturer of the oldest and largest in the world from Wolfsburg, Germany, and had begun to develop in 1937. Due to its age and history, Volkswagen became famous between people until they make their community. Surabaya which is the second largest city and is the largest trade center in Indonesia. Interior design of the